Normal Circulating PTH in Saudi Healthy Individuals with Hypovitaminosis D - Al-Saleh, Y.; Al-Daghri, N. M.; Alkharfy, K. M.; Al-Attas, O. S.; Alokail, M. S.; Al-Othman, A.; Sabico, S.; Chrousos, G. P. (Hormone and Metabolic Research, 2013)
Recent studies in the Middle East have shown an increased incidence of vitamin D deficiency across this region of year-round sunlight. There is scarcity of information, however, as to the levels of 1,25-dihydroxyvitamin D [1,25(OH)2D], the active form of vitamin D, and its associations with cardiometabolic parameters in an Arab cohort and this study aims to fill this gap. In a cross-sectional study, 33 male and 43 female (22 children and 54 adults, total 76) Saudis with previously established low levels of serum 25-hydroxyvitamin D [25(OH)D] (<50 ng/ml or 20 nmol/l) were recruited. Anthropometrics were obtained and fasting blood samples were taken for a routine measurement of glucose, lipid profile, calcium, and albumin, while serum 25(OH)D, 1,25-(OH)2D, and intact PTH were quantified using specific ELISAs. Serum calcium, intact PTH, and 1,25(OH)2D were all within the normal range in both children and adults in both genders. In all subjects, serum 1,25(OH)2D was not associated with intact PTH, while circulating 1,25(OH)D inversely correlated with systolic blood pressure (p=0.01) and waist circumference (p=0.04). Thus, vitamin D deficient Saudi children and adults with normal levels of 1,25-(OH)2D also had normal circulating calcium and PTH. This study suggests that local cutoffs should be set that will be of clinical significance in the identification of those at true risk for harder end-points, such as secondary hyperparathyroidism and bone-related diseases.
Keywords: vitamin D; 1, 25-dihydroxyvitamin D; PTH; Saudi Arab